Konsentrasi Pasar, Dinamika Harga, dan Profitabilitas dalam Perbankan Indonesia: Sebuah Investigasi Empiris - Ramadhan, Syahril (Universitas Jakarta Internasional, 2024)
This research delves into Indonesia’s banking sector’s competitive landscape, examining bank mergers’ effects on performance through the Structure Conduct and Performance (SCP) hypothesis. By reshaping market structure, bank mergers influence subsequent bank behavior and performance. The findings highlight a discernible pattern: an uptick in market concentration accompanies a decline in prices within the banking sector. This implies that mergers often yield economies of scale, enabling banks to offer more competitive rates. However, this reduction in prices directly impacts bank profitability. Moreover, the concentration ratio, a pivotal metric in market analysis, emerges as a significant gauge of industry competition. Serving as a structural measure of competition, the concentration ratio depicts the market share held by leading banks. Intriguingly, diminished competition, as indicated by higher concentration ratios, correlates with decreased profitability for banks operating within this framework. This exploration of Indonesia’s banking sector reveals a nuanced interplay between market structure, bank conduct, and overall performance. Through the SCP hypothesis, the study elucidates how seemingly routine bank mergers can trigger a cascade of effects, influencing market dynamics, profitability, and competitive positioning. Based on thorough analysis, the study furnishes strategic insights for policymakers, industry stakeholders, and the banking community, offering a comprehensive understanding of the ramifications of market shifts and guiding strategies to navigate Indonesia’s banking landscape adeptly.